The Twisted Configuration of the Martian Magnetotail: MAVEN Observations - DiBraccio, Gina A.; Luhmann, Janet G.; Curry, Shannon M.; Espley, Jared R.; Xu, Shaosui; Mitchell, David L.; Ma, Yingjuan; Dong, Chuanfei; Gruesbeck, Jacob R.; Connerney, John E. P.; Harada, Yuki; Ruhunusiri, Suranga; et al. (Geophysical research letters, 2018)
Measurements provided by the Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft are analyzed to investigate the Martian magnetotail configuration as a function of interplanetary magnetic field (IMF) BY. We find that the magnetotail lobes exhibit a ~45deg twist, either clockwise or counterclockwise from the ecliptic plane, up to a few Mars radii downstream. Moreover, the associated cross-tail current sheet is rotated away from the expected location for a Venus-like induced magnetotail based on nominal IMF draping. Data-model comparisons using magnetohydrodynamic simulations are in good agreement with the observed tail twist. Model field line tracings indicate that a majority of the twisted tail lobes are composed of open field lines, surrounded by draped IMF. We infer that dayside magnetic reconnection between the crustal fields and draped IMF creates these open fields and may be responsible for the twisted tail configuration, similar to what is observed at Earth.